2022
DOI: 10.3390/brainsci12091161
|View full text |Cite
|
Sign up to set email alerts
|

Listening to 15 Hz Binaural Beats Enhances the Connectivity of Functional Brain Networks in the Mental Fatigue State—An EEG Study

Abstract: Introduction: It is clear that mental fatigue can have many negative impacts on individuals, such as impairing cognitive function or affecting performance. The aim of this study was to investigate the role of sound interventions in combating mental fatigue. Method: The subjects were assessed on various scales, a psychomotor vigilance task (PVT) task, and a 3 min resting-state electroencephalogram (EEG), followed by a 20 min mental fatigue–inducing task (Time Load Dual Back ,TloadDback), during which subjects i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Wang et al [ 9 ] showed that listening to 15 Hz binaural beats is a proven intervention for mental fatigue that can contribute to maintaining working memory function. Moreover, participants who underwent a 12-min BB stimulation of 9.55 Hz significantly increased their working memory capacity [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [ 9 ] showed that listening to 15 Hz binaural beats is a proven intervention for mental fatigue that can contribute to maintaining working memory function. Moreover, participants who underwent a 12-min BB stimulation of 9.55 Hz significantly increased their working memory capacity [ 10 ].…”
Section: Introductionmentioning
confidence: 99%